An investigation of the questions mathematics teachers use on exams - Mustafa Güler (Journal of Pedagogical Research, 2021)
The extent to which the targeted outcomes in education are achieved can be determined by the educational assessment process. Although various alternative ways of assessment have arisen in recent decades, written examinations are still widely used by teachers. This study aims to determine the quality of the questions used by middle school mathematics teachers on exams. Program for International Student Assessment (PISA) proficiency levels framework constitutes the theoretical framework of the study, in which the document analysis method is adopted. In this study, where a total of 1252 written questions were examined, it was observed that teachers mostly preferred open-ended questions in terms of question types. The analysis of the questions in terms of proficiency level showed that teachers mostly preferred the questions at Level 1 and Level 2 at low cognitive level. Level 5 and Level 6 questions were never encountered at all grade levels. In the light of results, some suggestions are made for further research.